2010
DOI: 10.1111/j.1467-8624.2010.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Black and Hispanic Children Benefit More From Preschool? Understanding Differences in Preschool Effects Across Racial Groups

Abstract: Recent studies suggest that the effects of attending preschool vary by race. These findings are difficult to interpret because the likelihood of enrolling a child in preschool also differs across groups. This study used newly released, nationally representative data to examine whether the impact of preschool participation at age 4 varies across racial groups after accounting for selection differences (N = 7,400). Among a subsample of children living below a poverty threshold, no racial differences in preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 47 publications
5
53
0
1
Order By: Relevance
“…The effect size of prekindergarten care for the overall measure of chronic absenteeism was 0.13 and was 0.10 for moderate and 0.17 for strong outcomes. These effects were consistent with (or slightly larger) other assessments of center-based care using secondary data (Bassok, 2010;Claessens, 2012;Loeb et al, 2007;Turney & Kao, 2009;Yamauchi & Leigh, 2011), though this was the first study addressing absence outcomes.…”
Section: Baseline Modelssupporting
confidence: 84%
See 1 more Smart Citation
“…The effect size of prekindergarten care for the overall measure of chronic absenteeism was 0.13 and was 0.10 for moderate and 0.17 for strong outcomes. These effects were consistent with (or slightly larger) other assessments of center-based care using secondary data (Bassok, 2010;Claessens, 2012;Loeb et al, 2007;Turney & Kao, 2009;Yamauchi & Leigh, 2011), though this was the first study addressing absence outcomes.…”
Section: Baseline Modelssupporting
confidence: 84%
“…A related limitation of this dataset was that its large size may have increased the possibility of finding statistically-significant effect sizes. Though the effect sizes were consistent with or larger than prior studies that also used non-experimental data to evaluate center-based care (e.g., Bassok, 2010;Claessens, 2012;Loeb et al, 2007;Turney & Kao, 2009;Yamauchi & Leigh, 2011), they were nonetheless smaller than those derived from experimental work on center-based care (e.g., Yoshikawa et al, 2013). Again, this urges for future experimental work to consider chronic absenteeism as an outcome in order to compare to the findings in this study.…”
Section: Limitations and Further Studysupporting
confidence: 50%
“…A variety of studies have detailed how quality preschools serving children from poor families can lift early learning. These effects at times are sustained as children move through schools and into the work force (e.g., Bassok, 2010;Currie, 1999;Fuller, 2007;Karoly and Gonzalez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a large and consistent body of evidence has shown that these programs have the potential to boost school readiness among young children, and that benefits are often most pronounced among low-income and minority children (e.g. Magnuson & Waldfogel, 2005;Bassok, 2010;.…”
Section: Enhanced Program Standards (North Carolina Division Of Childmentioning
confidence: 99%
“…While income and SES play a salient role in parents' child care decisions, it is striking that black families-whose income and home resources often mirror those of Hispanic families-actually attend center-based care at rates similar to white children (Radey & Brewster, 2007;Bassok, 2010). For instance, in 2014 39% of black children 3-5 were enrolled in preschool, compared with 41% of white children, and just 32% of Hispanic children (Kena et al, 2016).…”
Section: Factors That Contribute To Parent Selection Of Early Carementioning
confidence: 99%